Deficiencies of antithrombin, protein C and protein S – Practical experience in genetic analysis of a large patient cohort - Caspers, Michael; Pavlova, Anna; Driesen, Julia; Harbrecht, Ursula; Klamroth, Robert; Kadar, Janos; Fischer, Ronald; Matthes, Bettina Kemkes-; Oldenburg, Johannes (Thrombosis and Haemostasis, 2012)
Deficiencies of natural anticoagulant proteins including antithrombin (AT), protein C (PC) and protein S (PS) are important causes of inherited thrombophilia. This study aimed to report on the practical experience gained in performing genetic analyses of a large cohort of patients with AT, PC and PS deficiencies and to relate this knowledge to clinical application. We genotyped a large cohort of 709 unrelated patients with AT (231), PC (234) and PS (244) deficiencies referred to us by physicians throughout Germany. Mutations were detected by direct sequencing and multiplex ligation-dependent probe amplification (MLPA). The highest mutation detection rate (MDR) was found for the SERPINC1 gene (83.5%), followed by the PROC (69%) and PROS1 (43%) genes. Even at AT activities close to the normal range (75%), the MDR was 70%. Contrastingly, for PC and PS deficiencies, the MDR dropped significantly and mildly lowered to subnormal values. At PS activities >55% for PS no mutations were detected. Mutation profiles of all three genes were similar with the highest prevalence for missense mutations (63–78%), followed by nonsense (7–11%), splice-site mutations (7–13%), small deletions (1–8%), small insertions/duplications (1–4%) and large deletions (3–6%). In conclusion, genetic testing is a useful diagnostic tool for diagnosing thrombophilia. Based on our data, genetic analysis for patients with AT deficiency is indicated for all subnormal activities. In contrast, genotyping is not advisable for PC activities >70% and for PS activities >55%.
Keywords: Protein C; protein S; antithrombin; thrombophilia; genetic analysis